Convenient approach to ω-aminoalkylthiophenes. Issue 17 (27th April 2016) - Shvydenko, Tetiana; Nazarenko, Kostiantyn; Shvydenko, Kostiantyn; Filimonchuk, Serhii; Vlasenko, Yurii; Tolmachev, Andrei; Kostyuk, Aleksandr
Graphical abstract: Highlights: Five- through seven-membered cyclic enaminoesters. A facile method for the synthesis of ω-aminoalkylthiophenes. Intramolecular cyclization of ω-aminoalkylthiophenes. Thieno[2, 3- c ]azepine and thieno[2, 3- c ]azocine derivatives. Abstract: Starting from readily accessible cyclic enaminoesters, arylisothiocyanates and α-haloketones, a facile method for the synthesis of ω-aminoalkylthiophene hydrobromides was developed. It was shown that in the first step cyclic enaminoesters react with arylisothiocyanates exclusively at the enamine position. Upon treatment with base, free 5-aminopentylthiophenes were prepared. In the case of shorter alkyl substituents (4-aminobutyl and 3-aminopropyl) the free ω-aminoalkylthiophenes undergo intramolecular condensation of the amino and ketone groups affording novel fused heterocycles—thieno[2, 3- c ]azepine and thieno[2, 3- c ]azocine.